STRATEGI PENINGKATAN SUMBER PENDAPATAN ASLI DAERAH (PAD) (Studi Tentang Intensifikasi Dan Ekstensifikasi Pemungutan Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan di Kabupaten Pemalang) - Rachmwati, Diyah; Basukianto, Basukianto (Jurnal Ilmiah Telaah Manajemen, 2017)
Since the enacment of the law No. 28 of 2009 concerning Local Taxation and Charges, Local Government has gained the authority to manage the collection of land and building tax on urban and rural area (PBB-P2). This condition has encouraged local government to further explore the potential of Local Own-source Revenue (PAD) through PBB-P2 sector income.The main objective of this research is to identify as well as to make assessment the effectiveness of intensification efforts implemented by The local district government of Pemalang in maximizing the potential income from the collection of land and building tax on urban and rural area (PBB-P2) by using descriptive study with qualitative approach. The results of this study identified that the collection of PBB-P2 conducted by the DPPKAD of Pemalang covers urban and rural area. Several intensification efforts taken by The Pemalang Government include: improving land and building tax data base performance, making the tax collection process more effective, strenghtening supervision , administrative reform, strenghtening coordination with related agencies, public campaign, and procuring Mobile Tax Payment System. The effectiveness of the collection of PBB-P2 intensification that has been implemented by the DPPKAD of Pemalang showed the criteria